2021
DOI: 10.1371/journal.pone.0247483
|View full text |Cite
|
Sign up to set email alerts
|

Targeting interventions for HIV testing and treatment uptake: An attitudinal and behavioural segmentation of men aged 20–34 in KwaZulu-Natal and Mpumalanga, South Africa

Abstract: Despite recent improvements, men still have worse HIV outcomes than women in South Africa. This study describes how young men form distinct behavioural and attitudinal subgroups, and is intended to inform the design of targeted interventions to encourage HIV testing and initiation on antiretroviral therapy. Data were collected using a cross-sectional survey with questions on men’s attitudes, beliefs and behaviours around HIV/AIDS. A total of 2,019 men were randomly sampled from eight district municipalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Lastly, research has identified subgroups of patients with personal characteristics (e.g. younger men) that predispose them to progress more successfully through the care continuum [ 215 , 216 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, research has identified subgroups of patients with personal characteristics (e.g. younger men) that predispose them to progress more successfully through the care continuum [ 215 , 216 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we tailor interventions to men's unique needs and motivations, based on extensive formative work. While innovative interventions for men are underway, [19][20][21] few have rigorously tested the impact of male-tailored interventions on ART engagement. 37 Our study will measure adverse events including unwanted disclosure, end of a relationship, and/or intimate partner violence (IPV).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated service delivery models (DSD) are now being developed to improve men's ART engagement throughout SSA. [19][20][21] As DSDs for men are developed, it is critical that strategies be feasible and cost-effective to allow scale-up. A "one size fits all" model is not as effective as more nuanced approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the methods used have been previously presented. 17 In brief, between October 2018 and January 2019, a cross-sectional study was conducted in 8 district municipalities in Mpumalanga and KwaZulu-Natal Provinces including from 2,019 Black African men aged 20-34 years with less than a university-level education. Participants completed a survey of demographic characteristics, sexual behavior, engagement with HIV testing and treatment services, alcohol use, HIV knowledge, mental health, and attitudes to gender equity.…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
“…The quantitative segmentation study produced 5 subgroups or segments of men, based on their attitudes, beliefs, behaviors, and needs related to HIV testing and treatment (described in depth in Bell et al). 17…”
Section: Qualitative and Quantitative Studiesmentioning
confidence: 99%